Liability for Defective Software in South Africa - Marshall, Andrew (Department of Commercial Law, 2014)
"There is no such thing as error-free code." This is neither the favoured mantra of a software development guru, nor the refrain of the chairman of a multinational software company, but the consensus of those at the coalface of software development the world over. [...] This paradigm raises interesting questions for the lawyer. There is no other discipline that operates on this basis. [...] It is only the software developer who, because of the complexity of software code, as well as the unpredictable environment in which his software will be executed, admits that the chance of his creation not performing as intended under all circumstances is so high that he must assume there are faults in it. [...] The distinction in computer operations between hardware and software is well understood, and while I will be examining the liability for defective software, the reader would do well to bear in mind that software is often inextricably bound to the hardware that it serves.